The Organization that we make. The Universidad Centroccidental Lisandro Alvarado, sixty years of continuous action - Beatriz Carolina Carvajal; Iván Brito-López (Ágora de Heterodoxias)
We are building our reality with our actions. At the Universidad Centroccidental Lisandro Alvarado, have we understood that adverse contexts constitute not only threats, but also opportunities to deploy our creative capacities as a learning organization? In 1977, the Russian-born Belgian chemist Ilya Prigogine won the Nobel Prize in Chemistry for his contribution to understanding systems far from thermodynamic equilibrium. With his work, he opened an epistemological perspective in the discussion about dynamic, nonlinear systems